Fishes of Melanesia from New Guinea and the Solomons to Fiji. - Warren Burgess & Herbert R. Axelrod (Neptune City, New Jersey T.F.H. Publications, 1975)
Pacific marine fishes ; bk. 6
Keywords: Fishes--Melanesia.; Fishes--Melanesia--Identification.